2004
DOI: 10.1007/bf02382814
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric power of mixed electronic-ionic conductors III. Case of calcium titanate

Abstract: Abstract. The primary purpose of the present work is the determination of the thermopower component related to electronic charge carriers for undoped calcium titanate. The second purpose of this work is establishment of the relationship between this thermopower component and the electronic component of electrical conductivity. An essential part of the present study includes the determination of the thermopower components corresponding to different charge carriers (electrons, electron holes and ions). The deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The reported TE properties of pristine CaTiO 3 are mainly obtained through theoretical calculations. Attou et al predicted that the zT value of B-doped CaTiO 3 (B@Ca) can reach 0.56 at 800 K . Bak et al observed a n-p type transformation in the Seebeck coefficient of CaTiO 3 at high temperatures (1173–1323 K) under different oxygen partial pressures. , It indicates that the presence of oxygen vacancies can lead to an n -type conduction behavior. However, for experimental studies, CaTiO 3 sintered in air demonstrates a remarkably high resistance, resulting in extremely poor thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…The reported TE properties of pristine CaTiO 3 are mainly obtained through theoretical calculations. Attou et al predicted that the zT value of B-doped CaTiO 3 (B@Ca) can reach 0.56 at 800 K . Bak et al observed a n-p type transformation in the Seebeck coefficient of CaTiO 3 at high temperatures (1173–1323 K) under different oxygen partial pressures. , It indicates that the presence of oxygen vacancies can lead to an n -type conduction behavior. However, for experimental studies, CaTiO 3 sintered in air demonstrates a remarkably high resistance, resulting in extremely poor thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%